A Simple Cross-Linking/Mass Spectrometry Workflow for Studying System-wide Protein Interactions. - Götze, M.; Iacobucci, C.; Ihling, C.H.; Sinz, A. (Analytical Chemistry, 2019)
We present a cross-linking/mass spectrometry workflow for performing proteome-wide cross-linking analyses within 1 week. The workflow is based on the commercially available mass spectrometry-cleavable cross-linker disuccinimidyl dibutyric urea and can be employed by every lab having access to a mass spectrometer with tandem mass spectrometry capabilities. We provide an updated version 2.0 of the freeware software tool MeroX, available at www.StavroX.com , that allows us to conduct fully automated and reliable studies delivering insights into protein-protein interaction networks and protein conformations at the proteome level. We exemplify our optimized workflow for mapping protein-protein interaction networks in Drosophila melanogaster embryos on a system-wide level. From cross-linked Drosophila embryo extracts, we detected 29931 cross-link spectrum matches corresponding to 7436 unique cross-linked residues in biological triplicate experiments at a 1% false discovery rate. Among these, 1611 interprotein cross-linking sites were identified and yielded valuable information about protein-protein interactions. The 5825 remaining intraprotein cross-links yield information about the conformational landscape of proteins in their cellular environment.